PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENGGUNAAN MODEL PEMBELAJARAN BERBASIS MASALAH PADA SISWA KELAS VI SD NEGERI 1 WONOKROMO - Khusni Winarsih (Sangkalemo : The Elementary School Teacher Education Journal, 2023)
This study aims to improve students' mathematics learning outcomes by using a problem-based learning model for sixth graders at SD Negeri Wonokromo. This research is classroom action research. The design of this study uses the Kemmis & Mc Taggart model. The subjects in this study were grade VI students of SD Negeri Wonokromo, totaling 12 students and carried out in 2 cycles. The data collection instrument used tests to measure student learning outcomes. The data obtained in the pre-cycle were 4 students or 33% who had scored reaching the minimum completeness criteria (KKM). And in the first cycle there was an increase of 75% of students completing the KKM and in the second cycle it increased to 100% of students graduating.